MDiabetes initiative using text messages to improve lifestyle and health-seeking behaviour in India. Issue 4 (19th July 2018) - Ramachandran, Ambady; Kumar, Rajeev; Nanditha, Arun; Raghavan, Arun; Snehalatha, Chamukuttan; Krishnamoorthy, Satheesh; Joshi, Pradeep; Tesfaye, Fikru
Abstract : Background: Data on the use of mobile technology in public health are sparse. Text messaging is cost-effective in disseminating information to large communities. The Ministry of Health and Family Welfare, Government of India, initiated and executed this mDiabetes programme. Objectives: The main objective of this commissioned study was to test the feasibility of using mobile technology to reach a large number of people to improve their lifestyle and health-seeking behaviour. Participants' interest, acceptability and scope for improvement were assessed. Methods : This mDiabetes observational study was done in India between 2016 and 2017. Text messages inviting registrations were sent to 130 million people in the country, mostly to the working class. Respondents (n=107 548) were registered by dialling a given phone number (missed phone call) or through a website. Based on the response, participants were grouped into six categories: persons with diabetes, pregnant/lactating women, high-risk individuals, healthcare professionals, elderly and normal population. They received 90 messages on healthy living during the 6 months. The impact of intervention was assessed at the third and sixth months by feedback messages. Telephonic interviews were conducted at 1 year in a subpopulation (n=855). Results: The registered respondents, 31 725, were grouped into six categories. 21.4% had diabetes and 5.3% had multiple risk factors. 15.6% responded to feedback messages. Among them, 57.2% followed a healthy diet, 72.3% practised advice on physical activity, 51.9% screened for diabetes and 67.3% checked their glycaemic status. The telephonic interviews showed that the programme was feasible and acceptable. The participants suggested use of interactive voice response system for registration and motivation. Discussion and conclusion: The study demonstrated the feasibility and acceptability of mHealth in a large population to disseminate knowledge regarding diabetes and healthy lifestyle, and to improve health-seeking behaviour. It helped to identify the limitations and scope for future improvements.